Analysis of N6-Methyladenosine Methylome in Adenocarcinoma of Esophagogastric Junction - Huang, Jia-Bin; Hu, Bin-Bin; He, Rong; He, Lian; Zou, Chen; Man, Chang-Feng; Fan, Yu (Frontiers in Genetics, 2022)
Background: From previous studies, we found that there are more than 100 types of RNA modifications in RNA molecules. m6A methylation is the most common. The incidence rate of adenocarcinoma of the esophagogastric junction (AEG) at home and abroad has increased faster than that of stomach cancer at other sites in recent years. Here, we systematically analyze the modification pattern of m6A mRNA in adenocarcinoma at the esophagogastric junction. Methods: m6A sequencing, RNA sequencing, and bioinformatics analysis were used to describe the m6A modification pattern in adenocarcinoma and normal tissues at the esophagogastric junction. Results: In AEG samples, a total of 4,775 new m6A peaks appeared, and 3,054 peaks disappeared. The unique m6A-related genes in AEG are related to cancer-related pathways. There are hypermethylated or hypomethylated m6A peaks in AEG in differentially expressed mRNA transcripts. Conclusion: This study preliminarily constructed the first m6A full transcriptome map of human AEG. This has a guiding role in revealing the mechanism of m6A-mediated gene expression regulation.